Comprehensive 4D robustness evaluation for pencil beam scanned proton plans - Ribeiro, Cássia O.; Meijers, Arturs; Korevaar, Erik W.; Muijs, Christina T.; Both, Stefan; Langendijk, Johannes A.; Knopf, Antje (Radiotherapy and oncology, 2019)
Due to anticipated clinical benefits, moving targets are potential future indications for pencil beam scanned proton therapy (PBS-PT). However, currently they are not widely treated at PBS-PT facilities due to dosimetric uncertainties caused by motion. We developed a method, the 4D robustness evaluation method (4DREM), to realistically and efficiently assess all possible events impacting PBS-PT treatments in the thorax. Using the 4DREM in large cohorts of lung and oesophageal cancer patients, it will become possible to illustrate, in clinical practice, how to trigger robustness settings for plan optimisation and to select and apply motion mitigation techniques.